Education, Prevention and Mother-Child Promotion in Oral Health: Experience Report in an University Hospital in Brazilian Southeast - Campaner Ferrari Bernardy, Catia; Sousa de Almeida, Juliana; Scheller de Oliveira, Lethicia; da Silva, Ana Maria; de Mello Rodrigues, Juliana Cristina; Marques Alves, Emily (Guará Journal, 2019)
The  article  reports  the  lived  experience  in  an extension  project.  This  project  was  focused  in mother and  children's  oral  health for pregnant women, puerperal, children and babies, which were hospitalised in University Hospital Cassiano Antônio Moraes (HUCAM) in Vitoria, ES, Brazil. The project is developed by  teachers and  academics of the dentistry course from Universidade Federal do  Espírito  Santo  (Ufes),  since 2010.  The  project  started  with  a  bibliographic  survey about  coletive  oral  health  and    subsequent  monthly group  discussion,  building  the  theoretical  foundations for  planning  and  development  of  the  activities.  The colective  accomodations  of    the  maternity  and children  ambulatory  were  visited   weekly,   under   the teacher's   supervision.   Orientations   about oral hygiene for mothers, newborn and children were given by the students. They also answered to people's questions weekly or  everytime  that  a  visit  occured. They  also  were  there  to  give  informations about the dentristry services offered by the hospital and  the university.    Around  1455  people  were  supported  by the  project  between  2010  and  2018.  Although  some mothers  had  a  lack of interest in the beginning to receive the information, many were  very  receptive during  the  meeting.  The  project  proved  to  be important  for  the  promotion  of  oral  health  of  these pregnant  women,  postpartum  women,  infants  and children,  by  the  early  insertion   of   oral   health   care, mainly   by   the   mothers'   direct   orientation by our dentistry students.
Keywords: Babies; Oral health; Pregnant women